2004
DOI: 10.1016/j.febslet.2004.09.085
|View full text |Cite
|
Sign up to set email alerts
|

Genistein induces Gadd45 gene and G2/M cell cycle arrest in the DU145 human prostate cancer cell line

Abstract: Genistein is the most abundant isoflavone of soybeans and has been shown to cause growth arrest in various human cancer cell lines. However, the precise mechanism for this is still unclear. We report here that the growth arrest and DNA damage-inducible gene 45 (gadd45) gene is induced by genistein via its promoter in a DU145 human prostate cancer cell line. The binding of transcription factor nuclear factor-Y to the CCAAT site of the gadd45 promoter appears to be important for this activation by genistein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…the cell cycle at the G2/M phase in various human cancer cell lines (Matsukawa et al, 1993;Choi et al, 1998;Oki et al, 2004). Many studies of the well-established anti-proliferative activity of genistein have indicated that it causes G2/M-phase arrest (Constantinou et al, 1998;Chen and Donovan, 2004;Singletary and Ellington, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…the cell cycle at the G2/M phase in various human cancer cell lines (Matsukawa et al, 1993;Choi et al, 1998;Oki et al, 2004). Many studies of the well-established anti-proliferative activity of genistein have indicated that it causes G2/M-phase arrest (Constantinou et al, 1998;Chen and Donovan, 2004;Singletary and Ellington, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…The induction of genes expression from the Gadd45 family in mammalian cells after treatment with certain pharmacological agents, including compounds of plant origin, has been described. For example, among these compounds are resveratrol [76], curcumin [77], quercetin [78], kaempferol, luteolin and apigenin [79], genistein [80], epicatechin [81], and fucoxanthin [82,83].…”
Section: Discussionmentioning
confidence: 99%
“…Various approaches have been used to inhibit or down-regulate neoplastic growth of prostate cancer using suramin, taxol, genistein, erbstatin, soluble receptors, pseudo-ligands, monoclonal antibodies for tyrosine kinase receptors and synthetic receptor tyrosine kinase inhibitors [35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%